Alkali metal adsorption on metal surfaces: new insights from new tools. Issue 13 (12th November 2020) - Raghavan, Arjun; Slocombe, Louie; Spreinat, Alexander; Ward, David J.; Allison, William; Ellis, John; Jardine, Andrew P.; Sacchi, Marco; Avidor, Nadav
Abstract : A combined study of density functional theory calculations and 3 He spin echo spectroscopy, finds sodium to change adsorption site on Ru(0001), from hollow to top, as the coverage is reduced. Abstract : The adsorption of sodium on Ru(0001) is studied using 3 He spin-echo spectroscopy (HeSE), molecular dynamics simulations (MD) and density functional theory (DFT). In the multi-layer regime, an analysis of helium reflectivity, gives an electron–phonon coupling constant of λ = 0.64 ± 0.06. At sub-monolayer coverage, DFT calculations show that the preferred adsorption site changes from hollow site to top site as the supercell increases and the effective coverage, θ, is reduced from 0.25 to 0.0625 adsorbates per substrate atom. Energy barriers and adsorption geometries taken from DFT are used in molecular dynamics calculations to generate simulated data sets for comparison with measurements. We introduce a new Bayesian method of analysis that compares measurement and model directly, without assuming analytic lineshapes. The value of adsorbate–substrate energy exchange rate (friction) in the MD simulation is the sole variable parameter. Experimental data at a coverage θ = 0.028 compares well with the low-coverage DFT result, giving an effective activation barrier E eff = 46 ± 4 meV with a friction γ = 0.3 ps −1 . Better fits to the data can be achieved by including additional variable parameters, but in all cases, the mechanism of diffusion is predominantly on a Bravais lattice, suggesting a single adsorption site in the unit cell, despite the close packed geometry.